Street-level discretion and adaptive strategies in indonesia’s free nutritious meal program - Eny Boedi Orbawati; Fadlurrahman; Ari Mukti; Joko Tri Nugraha (Jurnal Konseling dan Pendidikan, 2025)
Despite recent declines in prevalence, malnutrition and stunting remain persistent public health challenges in Indonesia. While existing studies on school feeding programs largely emphasize nutritional outcomes, they have given limited attention to how frontline actors translate policy into everyday practice. Addressing this gap, this study analyzes how street-level bureaucrats exercise discretion, negotiate structural constraints, and develop coping strategies in implementing the Free Nutritious Meal (MBG) Program in Magelang City and Magelang Regency. Using a qualitative case study design, data were collected through in-depth interviews with teachers, nutritionists, cooks, distribution drivers, and school staff, complemented by field observations. The data were coded thematically using key dimensions of Street-Level Bureaucracy as analytical categories, including discretion, resource constraints, coping practices, and social relations. The findings reveal that implementation is shaped not only by formal guidelines but also by localized adaptations. Teachers serve in dual roles as educators and informal nutrition supervisors, while cooks make creative adjustments to menu composition and portioning to ensure continuity despite limited facilities and fluctuating supplies. Frontline actors also employ social accountability mechanisms through close interaction with parents and local communities to sustain compliance and trust. These practices demonstrate how discretion operates as both a managerial necessity and a source of innovation. The study contributes to theory by extending Street-Level Bureaucracy to a developing-country context, highlighting how social accountability and collective coping practices shape policy outcomes beyond individual discretion. Practically, the findings inform policy refinement through targeted investments in facilities, streamlined administrative procedures, and adaptive menu planning to strengthen program sustainability.